Conducting polyanilline based paints on hot dip galvanized low carbon steel for corrosion protection - Deshpande, P.; Vagge, S.; Jagtap, Sharmili; Khiarnar, R.; Kelkar, Sarika A.; More, Minal (Bulgarian Chemical Communications, 2012)
Conducting polyaniline based paints have been applied on hot dip galvanized low carbon steel samples. The corrosion protection performance of these paint coatings was evaluated by using Tafel plots and impedance spectroscopy. It was found that the paint coatings offered significant corrosion protection to hot dip galvanized low carbon steel in aqueous 3.5 wt % NaCl solution.
Keywords: Conducting polyaniline based paints; corrosion prevention; hot dip galvanized low carbon steel

Comparison of methods for identifying periodically varying genes - Vijayan, V.; Deshpande, P.; Gadgil, Chetan J.; Gadgil, Mugdha (International Journal of Bioinformatics Research and Applications, 2013)